2019
DOI: 10.5603/arm.2019.0037
|View full text |Cite
|
Sign up to set email alerts
|

The TNF-α, P53 Protein Response and Lung Respiratory Changes Related to Exercise, Chronic Hypoxia and Adiantum capillus-Veneris Supplementation

Abstract: Introduction: Evidence suggests that hypoxia and high-intensity exercise training can increase apoptosis of lung cells and Adiantum capillus-veneris (Ac-v) extract can have anti-apoptotic effects. Thus, the aim of the present study was to investigate the effect of chronic hypoxia and the (Ac-v) extraction as a supplement on TNF-a and P53 protein expression as well as the respiratory surface. Material and methods: 24 healthy Wistar rats (age = 4 weeks, weight = 72 = 9 gr) were trained using interval training fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The phosphorylation of mutant p53 at Ser6/Ser9 by Ras/MAPK signaling is a crucial hallmark for TGF-β to switch to become a tumor promoter. N.sativa [43] and exercise training [44] are known as stimulators of p53 which can indirectly affect the expression behavior of TGFβ-1. In the present study, treatment with N.sativa and exercise training (E and NS+E groups), remarkably increased the gene expression of TGFβ-1 in healthy rats (E and NS+E) versus control subjects ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The phosphorylation of mutant p53 at Ser6/Ser9 by Ras/MAPK signaling is a crucial hallmark for TGF-β to switch to become a tumor promoter. N.sativa [43] and exercise training [44] are known as stimulators of p53 which can indirectly affect the expression behavior of TGFβ-1. In the present study, treatment with N.sativa and exercise training (E and NS+E groups), remarkably increased the gene expression of TGFβ-1 in healthy rats (E and NS+E) versus control subjects ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The study with the Andiantum capillus-veneris (Ac-v) extract, a species for which antiapoptotic activity has been described, demonstrated that in treated rats with 500 mL/g/kg body weight (bw)/day for 3 weeks exposed to hypoxic conditions, followed by 6 weeks of an interval training protocol, the expression of p53 protein and of TNF-α was reduced inversely, while the respiratory surface increased. These apoptotic indicators were altered under hypoxic conditions and treatment with the Ac-v extract acted against damaging events [ 43 ]. In relation to silymarin and the protective effects on lung tissue, in a model of acute lung damage by aspiration with hydrochloric acid (HCl) (1.2 mL/kg), oral treatment with silymarin at 200 mg/kg for 7 days reduced the indicators of histopathological damage caused in the lung by exposure to HCl.…”
Section: Discussionmentioning
confidence: 99%
“…In another study by Yadegari et al, the effect of chronic hypoxia and Adiantum capillusveneris supplements on protein response of P53, TNF-a and exercise -related respiratory changes were investigated and was shown that 3 weeks of exposure to hypoxia, after 6 weeks of exercise, increased P53 and TNF-a and decreased respiratory rate. After 3 weeks of taking Ac-v extract during exposure to hypoxia, the levels of P53 and TNF-a decreased and the level of respiration increased (95).…”
Section: Adiantummentioning
confidence: 97%
“…In a study of plant composition in northern Iran based on phytochemical tests, it was found that this plant contains tannins, flavonoids, terpenoids and unsaturated sterols (95). Separation of active ingredients was based on the presence of terpenoids and unsaturated sterols.…”
Section: Adiantummentioning
confidence: 99%
See 1 more Smart Citation